REPRESENTATION OF EDUCATIONAL FACILITIES AND THEIR RELATION TO ELEMENTS OF ECONOMIC CULTURE IN THE FILM LASKAR PELANGI - Siti Maesaroh Mlawati (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2023)
Currently, film is no longer interpreted as a work of visual art, but as a social representation and mass communication. In which there is a lot of social interaction to build a good film. While film can also be interpreted as a means to convey messages conveyed to the community. Film is a new facility for all humans to work both in writing and orally which can provide visualization into a film. So film as a means of mass communication also functions as a cultural transmission in society. Laskar Pelangi film with educational and social themes is understood as a representation of cultural reality that shows how a culture works and lives in a society. So that film can be said to be an effective medium in cultural learning by the community. This research is a cultural studies research with a subjective research approach. Through the unit of analysis in the form of the Laskar Pelangi film, this concept reflects a number of educational cultural findings such as the still weak education sector due to the uneven distribution of the education budget that is not optimal, the pretentiousness of education because it is more concerned with prestige than skills, lack of respect for the process, education is still measured from statistical figures. and the commercialization of education. Keywords: film, education, culture, economy